2014
DOI: 10.1042/bj20140485
|View full text |Cite
|
Sign up to set email alerts
|

[NiFe]-hydrogenase maturation in vitro: analysis of the roles of the HybG and HypD accessory proteins

Abstract: [NiFe]-hydrogenases (Hyd) bind a nickel-iron-based cofactor. The Fe ion of the cofactor is bound by two cyanide ligands and a single carbon monoxide ligand. Minimally six accessory proteins (HypA-HypF) are necessary for NiFe(CN)2CO cofactor biosynthesis in Escherichia coli. It has been shown that the anaerobically purified HypC-HypD-HypE scaffold complex carries the Fe(CN)2CO moiety of this cofactor. In the present study, we have purified the HybG-HypDE complex and used it to successfully reconstitute in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 57 publications
3
32
2
Order By: Relevance
“…Although HypE is supplied to the reaction mix in the form of the GDE complex, without the addition of extra His HypE (lane 2) to the reaction assay, only ϳ60% cleavage was detected. The cleavage of ϳ20% of HybC in the absence of His HypF (lane 3) can be explained by the presence of Fe(CN) 2 CO on the GDE complex (14). Notably, the maximal cleavage shown in lane 1 was achieved by the addition of equimolar ratio of purified Involved in acquisition and insertion of the nickel into large subunit HybC (53).…”
Section: The In Vitro System To Study [Nife]-hydrogenase Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HypE is supplied to the reaction mix in the form of the GDE complex, without the addition of extra His HypE (lane 2) to the reaction assay, only ϳ60% cleavage was detected. The cleavage of ϳ20% of HybC in the absence of His HypF (lane 3) can be explained by the presence of Fe(CN) 2 CO on the GDE complex (14). Notably, the maximal cleavage shown in lane 1 was achieved by the addition of equimolar ratio of purified Involved in acquisition and insertion of the nickel into large subunit HybC (53).…”
Section: The In Vitro System To Study [Nife]-hydrogenase Maturationmentioning
confidence: 99%
“…Fig. 1 presents our current working model for hydrogenase maturation and suggests the following sequence of events: (i) synthesis of CO and CN, ligation to iron, and incorporation of the fully coordinated iron into the large subunit pro-protein by the coordinated activity of HypCDEF (12); (ii) nickel insertion by concerted activity of HypA, HypB, and SlyD (6, 13) (these accessory proteins are not required at high Ni 2ϩ concentrations) (5,14); (iii) nickel acting as recognition site for a specific endopeptidase (15); cleavage of the C-terminal extension of the pro-protein that harbors the [NiFe]-cofactor, inducing conformational changes; and (iv) complex formation with the small subunit to yield active [NiFe]-hydrogenase (16,17).…”
mentioning
confidence: 99%
“…It was also shown that the HypC paralog HybG binds to the E. coli Hyd-2 large subunit precursor, which we term here pro-HybC (30,31). HybG is required for the maturation of hydrogen-oxidizing Hyd-2 and also functions in the maturation of the other hydrogen-oxidizing enzyme, Hyd-1, in the bacterium (30,32).…”
mentioning
confidence: 99%
“…Following this notion, the more crucial events with respect to the overall reaction rate arguably take place after formation of the HypCD‐complex, including the HypEF‐mediated, ATP‐dependent transcarbamoylation and dehydration reactions, the binding of cyanylated HypE to a preformed HypCD‐complex and the transfer of the Fe‐(CN) 2 CO‐group to HoxH. The molecular events leading to the assembly of the iron‐cofactor are currently under debate on the basis of the E. coli Hyp‐machinery (Soboh et al, ; Stripp et al, ; Stripp et al, ). Following entry of “modified” HypE into a functional ternary complex with the HypCD‐ or the homologous HybG‐HypD‐complex, redox chemistry affords transfer of the cyanide ligands, yielding the fully assembled Fe‐(CN) 2 CO‐group.…”
Section: Resultsmentioning
confidence: 99%